Pediatric Pyeloplasty in the Poor Function Kidneys: Does Surgical Success Guarantee Improvement in Renal Function? Single-Center Experience and Review of Literature - Sharifiaghdas, Farzaneh; Amini, Jalal; Narouie, Behzad; Rouientan, Hamidreza; Ahmadzade, Mohadese; Emami, Mohammad Aref (Urology Journal, 2024)
Purpose: To investigate the effect of pyeloplasty in pediatric patients with poor function kidneys, focusing on the split renal function (SRF) and anteroposterior diameter (APD) of the renal pelvis. Materials and Methods: A retrospective study included 47 pediatric patients with ureteropelvic junction obstruction (UPJO) who underwent open pyeloplasty with SRF< 20%. All patients were recruited from the Labbafinejad University Hospital center from April 2014 to October 2020. The results of preoperative ultrasonography and Diethylenetriamine pentaacetate (DTPA) scan compared with the results of the ultrasonography and DTPA scan 6 months and one year after surgery. Finally, Wilcoxon signed-rank test was used to test differences the SPSS (version 25) software statistical computer package. Results: The mean age of participants was 1.5 years. There were 34 cases with SRF between 10% and 20%, and 13 cases with SRF < 10%. The findings showed that pyeloplasty for UPJO leads to a significant improvement in renal function in poorly functioning renal units with 10% ≤ SRF < 20%. Although improvement in renal function occurred in the group with SRF of less than 10%, it was not statistically significant. The APD in both groups was statistically significantly improved. No correlation between genders and outcomes was found. Conclusion: Poorly functioning renal unit (SRF < 20%) can show functional improvement after the pyeloplasty.